Toxicité subChronique des Nanoparticule de ZnO chez Helix aspersa: Etude physiologique et Comportementale - Grara, N; Khaldi, F; Benamara, A; Zenir, Z; Abdemadjid, S; Bouloudenine, M (My University, 2017)
In this study we were interested in assessing the impact of ZnO based metal nanoparticles and their effects on body bioaccumulative bioindicator of environmental pollution and an indicator of health status Helix aspersa for the preservation of Human health. This is a sub chronic (28 days) by means of digestive absorption. The toxicity of ZnO is determined in the snail Helix aspersa using a bioassay conducted on laboratory animals exposed to increasing concentrations of ZnO (500 µg/g, 1000 µg/g, 5000 µg/g, 10000 µg/g, 15000 µg/g).Initial results show that the presence of metallic nanoparticles to ZnO growth caused an inhibition dosedependent in the shell diameter. The growth inhibition is also represented by a reduction dose - dependent on the weight of organs especially Soft (digestive gland and kidney), and reduced dose - dependent consumption rate and dry weight of the waste and compartmental disturbances were noted